157k views
4 votes
-2/3x + 9 = 4/3x -3​

2 Answers

5 votes

Answer:

x = 6

Explanation:

To solve, move all the x’s to one side and all the numbers. Remember when moving numbers to the other side of an equation, the sign changes from either a positive to a negative or vise versa.

9 + 3 = 4/3x + 2/3x

Next, add the like terms.

9+3=12

When adding fractions, add the numerator (top number), but first change denominator (bottom number) if not the same. Here, we don’t need to.

4/3x+2/3x=6/3x

So,

12 = 6/3x

Then, we have to divide each side by 6/3 to make the x alone.

12/6/3 = 6/3x/6/3

To divide with fractions, multiply the reciprocal (opposite number on number line):

12/1·3/6 = x

36/6 = x

6 = x

User Mviereck
by
5.2k points
2 votes

Answer:

Explanation:

User PatS
by
5.8k points